Effectiveness of disinfecting K-file contaminated with Staphylococcus aureus using alcohol, chlorhexidine, and sodium hypochlorite in different concentrations and durations: Efektivitas desinfeksi K-file yang terkontaminasi Staphylococcus aureus menggunakan alkohol, klorheksidin, dan natrium hipoklorit dengan konsentrasi dan durasi yang berbeda-beda - Tanumihardja, Maria; Hasan, Khaerunnisa; Sartika; Gunawan, Muh. Ibra Ikhza (Makassar Dental Journal, 2025)
This study evaluated the effectiveness of K-files contaminated with Staphylococcus aureus and immersion in alcohol, chlorhexi-dine, and sodium hypochlorite through CFU counting. Bacteria were identified through Gram staining and dilution to obtain an ini-tial 300 CFU, then the K-files were contaminated with bacteria. The samples were divided into three groups and repeated several times in a time series. For alcohol, the groups were divided into 70% and 96% concentrations. For chlorhexidine and sodium hy-pochlorite, each concentration was divided into three groups, and CFU counting was performed manually. The CFU results after immersion in 70% alcohol for 5, 10, and 15 minutes were 28 CFU, 5 CFU, and 0 CFU; 96% alcohol was 5 CFU, 1 CFU, and 0 CFU; 0.5%, 1%, and 2% chlorhexidine for 5 minutes and 10 minutes were 0 CFU; 0.25% sodium hypochlorite was 3 CFU, and for 10 minutes was 1 CFU; 0.5% and 1% sodium hypochlorite for 5 minutes and 10 minutes were 0 CFU. It was concluded that the antibacterial effectiveness of alcohol and sodium hypochlorite against S.aureus increased with increasing disinfectant concen-tration and K-file immersion time, while chlorhexidine was effective in killing S.aureus at a concentration of 0.5%. All disinfectants were effective for K-file disinfection.